Motor Vehicle Tax Management in North Maluku Province - Muhammad Zein Albugis; Abdul Hadi Sirait; Suwito (Jurnal Economic Resource, 2022)
The purpose of this study was to determine the obstacles faced in the implementation of Motor Vehicle Tax Management in North Maluku Province, especially at UPTD SAMSAT Ternate City and North Halmahera, the obstacles faced in Motor Vehicle Tax Management and efforts to overcome these obstacles. The data analysis technique used is qualitative research with an analytical descriptive approach. The results showed that the management of motorized vehicle tax in North Maluku Province, especially at UPTD SAMSAT, Ternate City and North Halmahera was in accordance with applicable regulations, and tax revenues were also quite large. Even so, there are still obstacles to tax management, both external and internal. There have been several efforts made to improve and optimize regional income from the motor vehicle tax sector, especially in terms of reforming the organization, improving the quality of Human Resources and improving facilities and infrastructure, which, of course will involve all stakeholders.